Removal of Toxic Pollutants from Aqueous Solutions by Adsorption onto an Organobentonite - Araceli Jacobo-Azuara; Roberto Leyva-Ramos; Erika Padilla-Ortega; Antonio Aragón-Piña; Rosa Maria Guerrero-Coronado; Jovita Mendoza-Barron (Adsorption Science & Technology)
An organobentonite was prepared by adsorbing the cationic surfactant hexadecyltrimethylammonium bromide (HDTMA) onto the surface of a calcium bentonite. The adsorption capacity of the organobentonite towards 2,4-dichlorophenoxyacetic acid (2,4-D), phenol and the dichromate ion (HCrO − 4 ) from aqueous solutions was investigated. The Langmuir isotherm gave a reasonable fit to the experimental data for the sorption of 2,4-D, phenol and the HCrO − 4 ion onto the organobentonite. The adsorption equilibrium data for 2,4-D demonstrated bimodal adsorption for equilibrium concentrations of 2,4-D greater than 650 mg/l. The capacity of the organobentonite for sorbing 2,4-D, phenol and the HCrO − 4 ion was considerably higher than that of the bentonite. This capacity was compared to that of a commercial activated carbon (F-400), from which it was concluded that modification of the bentonite substantially enhanced its adsorption capacity whereas the capacity of the organobentonite was lower than that of the F-400 carbon.